2018
DOI: 10.3389/fpls.2018.01015
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of PpBGAL10 and PpBGAL16 Delays Fruit Softening in Peach by Reducing Polygalacturonase and Pectin Methylesterase Activity

Abstract: β-galactosidases are cell wall hydrolases that play an important role in fruit softening. However, PpBGALs mechanism impacting on ethylene-dependent peach fruit softening was still unclear. In this study, we found that PpBGAL4, -6, -8, -10, -16, and -17 may be required for ethylene-dependent peach softening and PpBGAL10, -16 may make a main contribution to it among 17 PpBGALs. Utilization of virus-induced gene silencing (VIGS) showed that fruits were firmer than those of the control at 4 and 6 days after harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 70 publications
1
23
0
Order By: Relevance
“…In this study, first, the postharvest properties of ultra-late maturing peach cultivars TH and DJ were investigated. Generally, peach is considered to be a climacteric fruit in which ripening-related phenomena, such as accelerated endogenous ethylene biosynthesis and fruit softening, were reported to be controlled by ethylene (Hayama et al, 2006; Liguori et al, 2004; Liu et al, 2018). TH exhibited the characteristics of normal MF peach fruit, including rapid fruit softening leading to MF texture associated with an increase in endogenous ethylene production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, first, the postharvest properties of ultra-late maturing peach cultivars TH and DJ were investigated. Generally, peach is considered to be a climacteric fruit in which ripening-related phenomena, such as accelerated endogenous ethylene biosynthesis and fruit softening, were reported to be controlled by ethylene (Hayama et al, 2006; Liguori et al, 2004; Liu et al, 2018). TH exhibited the characteristics of normal MF peach fruit, including rapid fruit softening leading to MF texture associated with an increase in endogenous ethylene production.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, this concentration of propylene is equivalent to 50 ppm of ethylene and is sufficient to induce ethylene response in climacteric fruits (McMurchie et al, 1972; Burg and Burg, 1967). Indeed, in peach fruit treated with 500 ppm to 5,000 ppm of propylene, induction of autocatalytic ethylene production and dramatic fruit softening were reported (Liu et al, 2018; Yoshioka et al, 2010). In this study, DJ exhibited only a slight decrease in flesh firmness and maintained almost similar firmness to that at harvest even after seven days of continuous propylene treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nine cDNA libraries were constructed, and 47.05, 46.92, and 54.00 million raw sequence reads were generated from the PS, PM, and PL libraries, respectively. After removing low-quality reads and adaptor sequences, 46 Table 1). The resulting A. trifoliata transcriptome contained 241,376 transcripts, ranging from 201 to 2000 bp, and 186,054 unigenes (> 200 bp; Table 1 and Fig.…”
Section: Transcriptomic Analysis Overviewmentioning
confidence: 99%
“…Researchers have found that several cell wall modi cation genes, including β-GAL, β-GLU, PE, and PG are differentially expressed in cracked fruits compared with levels in non-cracking litchi fruits [21]. Downregulation of PpBGAL can delay peach fruit softening by reducing PG and pectin methylesterase activity [46]. Antisense inhibition of PE and PG activity in tomatoes was found to reduce fruit cracking [47].…”
Section: Candidate Degs and Daps May Play Key Roles In Fruit Pericarpmentioning
confidence: 99%
“…Finally, the gene function can be assessed based on the plant phenotype and physiological index alteration [9]. VIGS can be developed rapidly and has been applied to functional gene identi cation in eshy fruits, such as tomato [8,10], strawberry [11][12][13], apple [14][15], grape [16], citrus [17], loquat [18], pear [19][20], peach [21][22] , and sweet cherry [23][24]. However, there are no reports on VIGS in banana.…”
Section: Introductionmentioning
confidence: 99%